2011
DOI: 10.7763/ijtef.2011.v2.129
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Brand Equity in Indian CarManufacturing Firms

Abstract: Abstract-Brands have become increasingly important components of culture and the economy, now being described as "cultural accessories and personal philosophies". Brand Building process is a value addition technique which projects the image of the product, the company and the country at large. To study the problem effectively, car industry is chosen taking into the account the emergence of many new brands of the car product in the recent past. The objective of the study is to describe the measuring Models of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In other words, functional brand image explains consumers’ evaluation of a brand in a way that has to do with the performance and utility of the brand. Drawing from studies that have examined consumers’ attitudes and associations of automotive brands, functional brand image of automotive brands revolves around perceived quality (Chiu et al , 2015; Kiyani et al , 2012; Mahfooz, 2015; Murtiasih and Siringoringo, 2013; Santoso and Cahyadi, 2014; Thiripurasundari and Natarajan, 2011; Verhoef et al , 2007), customer satisfaction (Fetscherin and Toncar, 2009), product attributes (Thiripurasundari and Natarajan, 2011) and brand application (Thiripurasundari and Natarajan, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, functional brand image explains consumers’ evaluation of a brand in a way that has to do with the performance and utility of the brand. Drawing from studies that have examined consumers’ attitudes and associations of automotive brands, functional brand image of automotive brands revolves around perceived quality (Chiu et al , 2015; Kiyani et al , 2012; Mahfooz, 2015; Murtiasih and Siringoringo, 2013; Santoso and Cahyadi, 2014; Thiripurasundari and Natarajan, 2011; Verhoef et al , 2007), customer satisfaction (Fetscherin and Toncar, 2009), product attributes (Thiripurasundari and Natarajan, 2011) and brand application (Thiripurasundari and Natarajan, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…H4. Sales promotion has significant influence towards WOM 2.3 Influence of CBBE towards re-purchase intention and WOM Thiripurasundari and Natarajan (2011) reported that the five factors of brand equity (brand knowledge, brand association, brand application, brand preference and loyalty) had influence towards purchasing behavior. Brand application is the most important factor in the automotive industry in Puducherry, India.…”
Section: Intensive Distribution and Sales Promotionmentioning
confidence: 99%
“…The power of brands depends on the impression of the consumers. If consumers have better impression to the brands, the satisfaction and royalty will be higher (Thiripurasundari and Natarajan, 2011). The brand image becomes the major factor driving the consumption of the consumers.…”
Section: Introductionmentioning
confidence: 99%